Islamic bank financing and economic growth: the Malaysia experience - Chong, Su Cheing; Ke, Wan Ping; Koh, Cheng Lin; Koh, Hui Syin; Lim, Kai Xin (2020)
The main purpose of this research is to determine the cointegration and long run relationship between the Islamic banks’ financing and macroeconomic variables in Malaysia. The macroeconomic variables consist of Gross Domestic Product (GDP), Gross Fixed Capital Formation (GFCF), Foreign Direct Investment (FDI), Trade (TRADE) and Inflation (INF). This study also examines the causal relationship between the independent variables and dependent variables. There are 36 sample size and the quarterly data are collected from Bank Negara Malaysia and IMF’s International Financial Statistics from period 2010 Q1 to 2018 Q4. In addition, for the review of methodology of framework, the relationship between the variables is investigated by using Johansen Cointegration test, Vector Error Correction Model (VECM), Granger Causality test and also Impulse Response Function. The result showed that IBF with both GDP and TRADE have cointegration in long run. Furthermore, IBF are cointegrated with FDI and INF in a short run. However, there is no cointegration relationship between IBF and GFCF. Not only that, the results of these findings can convey a lot of useful information to some parties like policymakers, investors and also government.